Alternative PDGFD rearrangements in dermatofibrosarcomas protuberans without PDGFB fusions. (November 2018) - Dadone-Montaudié, Bérengère; Alberti, Laurent; Duc, Adeline; Delespaul, Lucile; Lesluyes, Tom; Pérot, Gaëlle; Lançon, Agnès; Paindavoine, Sandrine; Di Mauro, Ilaria; Blay, Jean-Yves; Fouchardière, Arnaud; Chibon, Frédéric; et al.
Abstract Dermatofibrosarcoma protuberans is underlined by recurrentcollagen type I alpha 1 chain- platelet-derived growth factor B chain (COL1A1-PDGFB ) fusions but ~ 4% of typical dermatofibrosarcoma protuberans remain negative for this translocation in routine molecular screening. We investigated a series of 21 cases not associated with the pathognomonicCOL1A1-PDGFB fusion on routine fluorescence in situ hybridization (FISH) testing. All cases displayed morphological and clinical features consistent with the diagnosis of dermatofibrosarcoma protuberans. RNA-sequencing analysis was successful in 20 cases. The classicalCOL1A1-PDGFB fusion was present in 40% of cases (n  = 8/20), and subsequently confirmed with aCOL1A1 break-apart FISH probe in all but one case (n  = 7/8). 55% of cases (n  = 11/20) displayed novelPDGFD rearrangements;PDGFD being fused either to the 5′ part ofCOL6A3 (2q37.3) (n  = 9/11) orEMILIN2 (18p11) (n  = 2/11). All rearrangements led to in-frame fusion transcripts and were confirmed at genomic level by FISH and/or array-comparative genomic hybridization.PDGFD -rearranged dermatofibrosarcoma protuberans presented clinical outcomes similar to typical dermatofibrosarcoma protuberans. Notably, the twoEMILIN2-PDGFD cases displayed fibrosarcomatous transformation and homozygous deletions ofCDKN2A at genomic level. We report the first recurrent molecular variant of dermatofibrosarcoma protuberans involvingPDGFD, which functionally mimic bona fide COL1A1-PDGFB fusions, leading presumably to a similar autocrine loop-stimulating PDGFRB. This study also emphasizes thatCOL1A1-PDGFB fusions can be cytogenetically cryptic on FISH testing in a subset of cases, thereby representing a diagnostic pitfall that pathologists should be aware of.